Prolonged herpes simplex virus latency in vitro after treatment of infected cells with acyclovir and human leukocyte interferon. - Scheck, A C (1986)
We previously demonstrated that herpes simplex virus type 1 (HSV-1) can be established in a latent form in vitro by the treatment of HSV-infected human cells with (E)-5-(2-bromovinyl)-2'-deoxyuridine (BVDU) in combination with human leukocyte interferon (IFN-alpha). We now report that the substitution of BVDU with 9-[(2-hydoxyethoxy)methyl]guanine (acyclovir; ACV) during a combined treatment with IFN-alpha inhibited HSV-1 replication and established in vitro virus latency that could be maintained for a longer period after inhibitor removal and a continued incubation at 37 degrees C. By contrast, the treatment of HSV-1-infected cells with combined IFN-alpha and 9-(1,3-dihydroxy-2-propoxymethyl)guanine, a congener of ACV, failed to establish in vitro virus latency. Furthermore, none of these inhibitors used alone was sufficient to establish in vitro virus latency. The use of nucleoside analogs differing from BVDU in their modes of action has enabled us to initiate studies designed to extend in vitro virus latency.